Analisis Faktor-Faktor yang Mempengaruhi Minat Konsumen terhadap Produk Pertanian Lokal dan Impor - Khosyi Juan Satria; Geby Dapot Tua Sipahutar; Lokot Muda Harahap; Mhd. Syaikhan Nazri Limbong; Helon Hibri Nababan; Jonathan Delvinosa Gultom (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The increasing presence of imported agricultural products in the domestic market has intensified competition and influenced consumer preferences toward local products. This study aims to examine the key factors affecting consumer interest in local and imported agricultural products by identifying patterns found in previous research. A qualitative approach was applied using a structured literature review method. Relevant sources were systematically selected from scientific journals, books, and academic publications published within the last decade, focusing on consumer behavior and agricultural product studies. The collected data were analyzed using content analysis to classify and interpret recurring themes across studies. The findings reveal that consumer interest is shaped by the interaction of economic, product-related, and socio-psychological factors. Price and freshness remain the main advantages of local products, while imported products are generally preferred due to consistent quality, better physical appearance, wider availability, and stronger branding strategies. In addition, social values and consumer perceptions significantly influence purchasing decisions. This study highlights the need for improving quality consistency, distribution systems, and marketing strategies to enhance the competitiveness of local agricultural products in the domestic market.